Perubahan Persepsi Remaja Setelah diberikan Pendidikan Kesehatan Menggunakan Media Audio Visual tentang Faktor Resiko Diabetes Melitus Tipe 2 - Maria Diah CT; Tri Cahyo S; Wiwin Martiningsih (Journal of Ners and Midwifery, 2014)
Wrong Perception is one of the risk factors of Diabetes Mellitus (DM) type 2 will make adolescent to do unhealthy lifestyle that leads to DM disease. Increasing knowledge through health education is expected to increase the perception. The purpose of research was to analyze adolescent’s perceptions changing after was given health education using audio visual media about risk factors of type 2 Diabetes Mellitus. The method in this research was experimental research with Quasi-Experimental design pretest-posttest. The sample consisted of 128 respondents, 64 respondents in control group and 64 respondents in the experimental group. Sampling was done by purposive sampling. The results showed an increasing perceptions average 2.31 in control group. In experimental group increased a perceptions average 3.44. Further analysis showed that health education using audio-visual media is more effective in improving perceptions. The conclusion of this research showed that using audio-visual media is more effective to increase the perception. Audio-visual media provide a more attractive appearance, so that there is a dynamic movement to attract the attention. The research recommended an increasing in preventive and promotive diabetes type 2 through health education and activities around school (SMU).